Response of diabetic feets{u06E5}pathogenic bacteria to heavy metal salts - Sara Mohamed Khalid Elshafie; Ibrahim Ali Emara; Mohamed Ez Eldin Abdelhaleem Dawoud (Cairo : Sara Mohamed Khalid Elshafie, 2016)
This investigation aimed at the study of the effect of heavy metals salts solutions on the pathogenic bacteria isolated from diabetic Feet's patients in early stages. Isolation and identification of isolated bacteria based on biochemical, morphological and molecular biology techniques (PCR using 16S rRNA primer). In this experiment, 27bacteria was isolated and identified; it included 8 Escherichia coli, 7 Staphylococcus spp., 5 Pseudomonas spp., 4 klebsiella spp. and 3 Proteus spp. Isolates was confirmed by 16S rRNA gene sequence analysis. Also these bacteria tested for susceptibility to commonly used antibiotics and found that mainly meropenem , and cephoperazone +sulbactam were the most effective antibiotics against bacteria. On studying the physiology and growth bactericidal response of these bacteria to different concentration of some selected heavy metal salts (e.g. Copper & Zinc) solutions with different concentrations (10 oM{u2013} 10p7 (BoM), Revealed that the most effective concentration of heavy metals salt solutions CuSO4 & ZnSO4 are (10p5 (BoM). These solutions were tested on the tissue of patients to make sure that these concentrations were nontoxic. After detection of the nontoxic& most inhibitory concentration to different pathogenic bacteria. These obtained results can be applied for treatment of diabetic feet's pathogenic bacteria as a lotions
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany and Microbiology
Issued also as CD
Keywords: Diabetic feet; Heavy metals; Pathogenic bacteria